Gingival recession and periodontal therapy - Monya N. Hassan; Maha A. Aziz (College of Dentistry/ University of Baghdad, 2019)
Background: Gingival recession is defined as the apical migration of the gingival margin below the cementoenamel junction (CEJ), resulting in exposure of the root surface and it is one of the main esthetic complaints of patients. The management of gingival recession and its sequelae is based on a thorough assessment of the etiological factors and the degree of tissue involvement.